Effects of seawater absorption and desorption on the long‐term creep performance of graphene oxide embedded glass fiber/epoxy composites. Issue 11 (6th August 2020) - Anand, Abhijeet; Ghosh, Sohan Kumar; Prusty, Rajesh Kumar
Abstract: This study is primarily focused on analyzing the consequences of sea water absorption and desorption on the long‐term durability of glass fiber/epoxy (GE) and 0.5 wt% graphene oxide (GO) dispersed glass fiber/epoxy (GO‐GE) composites. Both GE and GO‐GE composite specimens were initially exposed to natural seawater for a duration of 9 months. Desorption was also carried out for some of the seawater saturated samples. Before ageing, flexural test and dynamic mechanical analysis were carried out to understand the impact of GO incorporation on the characteristics of GE composite. Using gravimetric analysis, the seawater uptake kinetic curves were determined for both the composites. Long‐term durability was assessed by performing stepwise isothermal creep and recovery tests in 30°C to 120°C temperature range and analysis of the results involved the use of time‐temperature superposition principle for constructing the creep master isotherms in different conditions (before ageing or dry state, saturated state, and desorbed state). Abstract : Long‐term performance of Sea water resistance of graphene oxide embedded FRP Composites.